Establishment Of Embassy Relations and the Beginning of Political Relations (Central Asia and India) (Eurasian Journal of History, Geography and Economics, 2022)
This article provides information on the ancient history of relations between India and Central Asia and their socio-political status. With the help of this information, the life of the country and the people was studied in concrete figures in order to get a clear idea of the historical processes of that period.